The Role of Growth-Mindset and Interpersonal Communication in School Well-being: Self-Efficacy as a Mediator among Muslim Students - Wihartati, Wening; Nordin, Nor Akmar; Nurfitri, Aldila Dyas; Masfia, Irma (Islamic Guidance and Counseling Journal, 2026)
Concerns about the psychological well-being of university students, especially Muslim students in Indonesia and Malaysia, make it important to understand factors that can support their well-being on campus. This study employed a quantitative design with path analysis to test the mediating role of self-efficacy in the relationship between growth-mindset, interpersonal communication, and school well-being. Data were collected from 433 Muslim students (241 from Indonesia and 192 from Malaysia), aged 18–25 years, through purposive sampling. The sample consisted of 89 men and 344 women across different academic years. Four validated instruments were used: the Growth-Mindset Scale (8 items, α = 0.81), Interpersonal Communication Scale (38 items, α = 0.84), Self-Efficacy Scale (17 items, α = 0.88), and School Well-being Scale (43 items, α = 0.89). Data analysis was performed using Hayes’ PROCESS macro (Model 4). The results indicated that growth-mindset and interpersonal communication both positively influenced self-efficacy. However, neither growth-mindset nor interpersonal communication had a direct effect on school well-being. Instead, both factors exerted significant indirect effects through self-efficacy, indicating full mediation. These findings highlight the importance of strengthening self-efficacy by promoting a growth-mindset and enhancing interpersonal communication skills to improve students’ school well-being.